The South African general election of 1943 (Historia, 2021)
-
Keywords: Smuts J.C.; United Party; Politics; Dominion Party; Herenigde Nasionale Party; Labour Party; General Election 1943; Afrikaner Party; Coalition government; Volkseenheid candidates